How is loneliness related to anxiety and depression: A population‐based network analysis in the early lockdown period. (6th May 2022) - Owczarek, Marcin; Nolan, Emma; Shevlin, Mark; Butter, Sarah; Karatzias, Thanos; McBride, Orla; Murphy, Jamie; Vallieres, Frederique; Bentall, Richard; Martinez, Anton; Hyland, Philip
Abstract : High risk of mental health problems is associated with loneliness resulting from social distancing measures and "lockdowns" that have been imposed globally due to the COVID‐19 pandemic. This study explores the interconnectedness of loneliness, anxiety and depression on a symptom level using network analysis. A representative sample of participants ( N = 1041), who were of at least 18 years of age, was recruited from the Republic of Ireland (ROI). Loneliness, anxiety and depression were assessed using validated instruments. Network analysis was used to identify the network structure of loneliness, anxiety and depression. Loneliness was found to be largely isolated from anxiety and depression nodes in the network. Anxiety and depression were largely interconnected. "Trouble relaxing, " "feeling bad about oneself" and "not being able to stop or control worrying" were suggested as the most influential nodes of the network. Despite the expectation that loneliness would be implicated more robustly in the anxiety and depression network of symptoms, the results suggest loneliness as a distinct construct that is not interwoven with anxiety and depression.